The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1590/s0100-204x2006000800010
|View full text |Cite
|
Sign up to set email alerts
|

Cultivo de coco 'Anão Verde' irrigado com águas salinas

Abstract: Resumo -O objetivo deste trabalho foi estudar a viabilidade de utilização de águas de elevada salinidade na irrigação do coqueiro (Cocos nucifera L.) cv. Anão Verde, em fase inicial de produção, com 3,5 anos de cultivo. O experimento foi conduzido em blocos inteiramente casualizados, com quatro tratamentos, representados pelos níveis de salinidade da água de irrigação (condutividade elétrica -CEa = 0,1, 5,0, 10,0 e 15,0 dS m -1 a 25ºC) e cinco repetições. Constatou-se tendência de aumento do número de flores f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 10 publications
0
3
0
2
Order By: Relevance
“…Coconut palms are being planted in increasing numbers in arid and semi-arid zones of the Nordeste despite the inappropriate climate. Marinho et al investigated field irrigation using water at different salinity rates [(0.1; 5.0; 10.0; 15.0) dS·m -1 at 25°C] [69]. These authors demonstrated that, using the green dwarf variety, nuts can be harvested at 7 months if the salinity of the irrigation water is below 10 dS·m -1 .…”
Section: Influence Of Cultivation Practicesmentioning
confidence: 99%
“…Coconut palms are being planted in increasing numbers in arid and semi-arid zones of the Nordeste despite the inappropriate climate. Marinho et al investigated field irrigation using water at different salinity rates [(0.1; 5.0; 10.0; 15.0) dS·m -1 at 25°C] [69]. These authors demonstrated that, using the green dwarf variety, nuts can be harvested at 7 months if the salinity of the irrigation water is below 10 dS·m -1 .…”
Section: Influence Of Cultivation Practicesmentioning
confidence: 99%
“…In Brazil (5 • 46 S; 35 • 12 W; alt. 18 m asl), Marinho et al (2006) evaluated the viability of using saline water for irrigation. In a two year study with (initially) three and a half-year-old green dwarf coconut (cv.…”
Section: Drought Mitigationmentioning
confidence: 99%
“…Ferreira Neto et al (2002) aplicaram água com salinidade de até 15 dS m -1 e observaram que a CEes ficou acima de 4 dS m -1 , sem, contudo, comprometer a produtividade do coqueiro. Entretanto, Marinho et al (2006) observaram diminuição do peso e do núme-ro de frutos colhidos, quando a condutividade elétrica da água de irrigação foi maior que 5 dS m -1 .…”
Section: Resultsunclassified
“…Teixeira et al (2005b) concluíram que doses superiores a 240 kg ha -1 de N na forma de nitrato de amônio provocaram acidificação do solo, diminuindo a saturação por bases. O comportamento produtivo do coqueiro em resposta à salinidade no solo foi avaliado em pesquisas no Rio Grande do Norte e na Paraíba (Ferreira Neto et al, 2002;Marinho et al, 2006).…”
Section: Introductionunclassified